Enhanced Benefit of STA-MCA Bypass Surgery in Chronic Terminal Internal Carotid and/or Middle Cerebral Artery Occlusion Patients With Impaired Collateral Circulation: Introducing a Novel Assessment Approach for Collateral Compensation - Cheng Qiu; Yanping Zhang; Zhiqiang Yu; Yonghui Xu; Yongjiang Huang; Tianci Huang; Jun Ma; Jinbing Zhao (Emergency Medicine International)
Conclusion: STA-MCA bypass surgery improved neurological outcomes in CTI/MCAO patients, particularly those with poor preoperative collateral compensation. EFP may serve as a reliable, noninvasive tool for assessing collateral circulation status in this population.